Faktor - Faktor Yang Melatarbelakangi Pemberian Pasi Dini - Ferillia Adiesti (MEDICA MAJAPAHIT, 2016)
The improvement of lactation substitute usage (mother lactation substitution - PASI) for infant age less than 6 months old will be declining lactation involved. Limited knowledge, social economic and cultural social which supporting that mother's lactation is not enough for babies satisfied the baby rely on lactation substitute given early. This research aims to recognize any factors which background lactation substitute given early. Type of this research is descriptive, by using questionnaire instrument. Sample in this research are all mother who have babies 0-6 months old who give lactation substitute in Polindes DlangguÂ area, Dlanggu district, Mojokerto regency as much as 20 respondents. Technique used was total sampling. Collecting data done on October 30th until November 13th, 2010. Data analysis used in descriptive analysis by calculating frequency and describing in frequency distribution table form. The result of the research indicting that background of the factor of lactation substitute given early, are bad knowledge are about 13 respondents (65%), economy social level as high as 20 respondents (100%), and bad culture social are 13 respondents (65%). Knowledge is most important domain that formed behavior poor knowledge about lactation substitute, high level social economy and working mothers status boosted mothers to give lactation substitute early. Culture social influenced toward mother's behavior who consider her crying baby are unsatisfied baby then make mother to give early lactation substitution. A mother shall improve her knowledge time for giving lactation precisely and exactly, or health workers shall give information or consultation about exclusive lactation and lactation substitute exactly then could sustained lactation involved